How high will you climb? : determine your success by cultivating the right attitude - Maxwell, John C., 1947- (Nashville : Thomas Nelson, 2014)
John Maxwell shares insights from real-life experiences showing how to attain a great attitude to overcome life s difficulties, win people over, and turn problems into opportunities.
Originally published as: Your attitude. San Bernardino, Calif. : Here's Life Publishers, c1984.
Includes bibliographical references.
Keywords: Attitude (Psychology) -- Religious aspects -- Christianity; Actitud (Psicología). -- Aspectos religiosos -- Cristianismo; Vida cristiana; Christian life; Success -- Religious aspects -- Christianity